Peningkatan Produksi Madu Klanceng di Hutan Rakyat untuk Kesejahteraan Masyarakat dan Kelestarian Lingkungan di Kemalang, Klaten - Yus Andhini Bhekti Pertiwi; Dwi Apriyanto; Ana Agustina; Malihatun Nufus; Ike Nurjuita Nayasilana (Institut Pertanian Bogor, 2023)
Tlogowatu Village, Kemalang District, Klaten Regency, is located on the slopes of Merapi Mountain. Currently, sand and stone mining from Merapi Mountain is the primary commodity produced by Tlogowatu Village. If this condition continues, it will cause the damage to the environment. Therefore, several community leaders have cultivated the stingless bee (Trigona laeviceps) as an economic source while adhering to ecological principles through stingless bee farming in community forests. However, community forest and stingless beekeeping need to be appropriately managed, especially in terms of management, production, and marketing aspects. Activities are carried out in several stages, namely starting with pre-activity surveys, counselling and practical development of management, production and marketing aspects, as well as monitoring and evaluation of activities. This activity has increased the knowledge of target partners regarding the livestock of Clanceng in community forests in the form of another type of Clanceng, namely T. biroi, various feed sources, techniques for breaking up split rapid colonies, and good honey packaging. Apart from that, through klanceng livestock in community forests, local communities also gain ecological benefits and build potential for developing agricultural education tourism (edu-agro-tourism) areas.